Insects in agriculture - Juraimi, Abdul Shukor (Universiti Putra Malaysia, 2013)
Insects have got both positive and negative impacts in agriculture. Insects become pests when they interfere with our welfare, aesthetics or profits. A reduction or loss in yield and quality of crops is partly due to result of insect-feeding activities and as vector/host to pathogen transmissions. On the other hand, these small creatures serve us a lot as pollinating agents of many important agricultural crops, as biological controlling agents of pests and weeds as well as by producing honey, silk and many other materials essential to us.